Spectroscopic investigation of the reaction product of tetrathiazyldihydridofluoride (S4N4H2F2) with Cd(II) Chloride (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
The reaction of tetrathiazyldihydridofluoride  (S4N4H2F2) with Cd(II) Chloride was carried out  in organic medium the product obtained was  characterized on the basis of IR, UV, EPR, Mass  and 1H NMR Spectra and is formulated as  (S3N4H2F2CdCl)x where x=2.32
Keywords: Tetrathiazyldihydrofluoride; hydrogen-bonding; semiconductor